Engaging African ancestry participants in SLE clinical trials. Issue 1 (11th December 2018) - Anjorin, Aderike; Lipsky, Peter
Abstract : SLE is a complex autoimmune disease with genetic and clinical differences between patients that appear to reside along ancestral lines. Over the last 20 years, a preponderance of evidence has shown that SLE is more common and severe in minority populations, particularly in African ancestry (AA) women. However, in clinical trials for new therapies of SLE, AA is often under-represented. Without enrolling sufficient AA participants, it is difficult to ascertain the safety and efficacy of new potential therapies among individuals with SLE of different ancestries. Although enrolling minority populations in clinical trials has been a significant challenge for many reasons, the various stakeholders involved in clinical research could act within their own realms to develop new paradigms and policies to bolster the inclusion of AA in the development of new therapies.